2018
DOI: 10.1111/pde.13719
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oral manifestations of toxic epidermal necrolysis with low‐level laser therapy in a pediatric patient

Abstract: Drug‐induced reactions are complications associated with high mortality and significant morbidity. Stevens–Johnson Syndrome (SJS) and toxic epidermal necrolysis (TEN) are examples of these conditions, which are characterized by skin and mucous lesions. Here, we report a case of a 9‐year‐old girl who presented with blisters associated with an extensive vesicular rash and multiple ulcerations on the lips and oral cavity. A drug‐induced hypersensitivity reaction to antibiotics was suspected, and a diagnosis of TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
5
0
4
Order By: Relevance
“…Resulting in analgesic, anti-inflammatory effects and accelerating the wound healing process (Sonis et al, 2016). Some studies have already described positive results from the use of photobiomodulation in oral lesions of TEN and Steven Johnson Syndrome and demonstrated that there were analgesic effects and tissue regeneration (Simões et al, 2011;Rocha et al, 2019). It is also used in other ulcerative disorders such as mucositis and pemphigus vulgaris (Sonis et al, 2016;Dal Prá et al, 2020), photobiomodulation reduces the painful sensation, ensures comfort to the patient and reduces the prescription of analgesics (Soares et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resulting in analgesic, anti-inflammatory effects and accelerating the wound healing process (Sonis et al, 2016). Some studies have already described positive results from the use of photobiomodulation in oral lesions of TEN and Steven Johnson Syndrome and demonstrated that there were analgesic effects and tissue regeneration (Simões et al, 2011;Rocha et al, 2019). It is also used in other ulcerative disorders such as mucositis and pemphigus vulgaris (Sonis et al, 2016;Dal Prá et al, 2020), photobiomodulation reduces the painful sensation, ensures comfort to the patient and reduces the prescription of analgesics (Soares et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The photobiomodulation protocol was performed with a portable 100mW (InGaAIP -duo laser / MMOpstics, São Carlos, SP, Brazil) semiconductor device with red light (660 nm) and infrared (808 nm), using 2J for 4 seconds per point, with a distance of 1 cm between points, being applied over the entire length of oral lesions (Rocha et al, 2019). The total application per session was 5-8 minutes.…”
Section: Case Reportmentioning
confidence: 99%
“…The LLLT is a phototherapy that stimulate tissue regeneration, reduce inflammation, and control pain (Anschau et al, 2019). Previous reports described LLLT in the treatment of oral ulcers of a Stevens-Johnson syndrome patient exhibiting pain relief and improvement in oral functions (Simões et al, 2011;Rocha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, efeitos na transmissão do impulso nervoso, incluindo alterações no limiar de dor dos nociceptores, libertação de endorfinas e redução da dor aguda foram descritos. 14 Corroborando com os achados da literatura, a aplicação de fotobiomodulação complementar ao uso de elixires orais tópicos reduziu gradativamente as queixas de dor pelo paciente, permitindo a cura das lesões orais e retorno de função como fala e alimentação, não provocando formação de cicatrizes ou fibroses ao final do tratamento.…”
Section: Discussão E Conclusõesunclassified